Adverse Drug Reactions during COVID-19 Treatment: A Comprehensive Analysis Focused on Hospitalized Patients, with the Use of a Survey in Cuba in 2020. (1st February 2023) - Gil-del-Valle, Lizette; Gravier-Hernández, Rosario; Baldoquin-Rodríguez, Waldemar; Sierra-Vázquez, Beatriz; Perez-Díaz, Ana Beatriz; Sariol-Resik, Pablo; Prieto-Dominguez, Tatiana; Delgado-Guerra, Mario Manuel; Sánchez- Márquez, Joniel Arnoldo; López-Fernández, Olga Elena; Fonseca-Betancourt, Faustina; Valdés-Lanza, Liana; et al.
Abstract : Context . Off-label, compassionate use of potential drugs against SARS-CoV-2 acute infection could modify their safety profiles. Aims . To evaluate the prevalence and type of adverse drug reactions (ADRs), together with associated risk factors, among Cuban COVID-19 patients treated with chloroquine (CQ), lopinavir/ritonavir (LPV/r), or interferon α 2b (IFN α 2b), according to the Cuban protocol. Materials and Methods . A prospective descriptive analysis of ADRs was performed on 200 COVID-19 patients who were admitted consecutively to three hospitals in Havana and Pinar del Río from April to July 2020. Information on demographics, ADRs, outcomes, behavioral, and health-related factors was collected using a validated questionnaire and clinical records. Each potential ADR case was assessed for causality based on the WHO-UMC algorithm, concomitant drug influences, and the presence of any drug-drug interactions (DDI). Results . The total frequency of ADRs was 55%, with predominantly gastrointestinal disorders and general symptoms (23% vs 20%). 95.1% of ADRs occurred within 10 days after treatment and 42 potential DDI in 55.5% of patients (61/110) were observed. The prevalence of ADRs was: 44%, 30.4%, and 26.4% for IFN α 2b, LPV/r, and CQ, respectively. Sex (odds ratio (OR): 0.40 (95% confidence interval (CI): 0.211–0.742), age (OR: 2.36 (95% CI: 1.02–5.44)), and underlying diseases (OR: 0.12 (95% CI: 0.06–0.23)) were independently associated factors for ADRs (P < 0.05 ). Conclusions . The frequency of ADRs and potential DDI was high compared to their use during nonpandemic times (e.g., for malaria, HIV, or inflammatory diseases). The safety profile of these drugs when used for COVID-19 treatment showed similar characteristics. Comorbidities, age >37 years old, and female sex were associated with ADRs.